Looking for multiple equilibria when geography matters : German city growth and the WWII shock - E. Maarten Bosker; Steven Brakman; Harry Garretsen; Marc Schramm (Center for Economic Studies and ifo Institute (CESifo), 2005)
Many modern trade and growth models are characterized by multiple equilibria. In theory the analysis of multiple equilibria is possible, but in practice it is difficult to test for the presence of multiple equilibria. Based on the methodology developed by Davis and Weinstein (2004) for the case of Japanese cities and WWII, we look for multiple equilibria in a model of German city growth. The strategic bombing of Germany during WWII enables us to assess the empirical relevance of multiple equilibria in a model of city-growth. In doing so, and in addition to the Davis and Weinstein framework, we look at the spatial inter-dependencies between cities. The main findings are twofold. First, multiple equilibria seem to be present in German city growth. Our evidence supports a model with 2 stable equilibria. Second, the explicit inclusion of geography matters. Evidence for multiple equilibria is weaker when spatial interdependencies are not taken into account.
Keywords: R12; R11; F12; 330; Stadtwachstum; Räumliche Interaktion; Räumliche Gleichgewichtstheorie; Gleichgewicht; Schätzung; Deutschland <bis 1945>